Sensory Assessment by Consumers of Traditional and Potentially Probiotic Green Spanish-Style Table Olives - López-López, Antonio; Moreno-Baquero, José M.; Rodríguez-Gómez, Francisco; García-García, Pedro; Garrido-Fernández, Antonio (Frontiers in Nutrition, 2018)
This work presents the sensory characterisation by consumers of traditionally and potentially probiotic green Spanish-style table olives.To this aim, green Manzanilla olives from the same lot were debittered, washed, and brined in the same way; then, one sub-lot was allowed fermenting spontaneously while another one was inoculated with a putative probiotic bacterium (Lactobacillus pentosus TOMC-LAB2). After fermentation, the olives from both sub-lots were packed with fresh brine to reach 5.5 g/100mL NaCl and 0.6 g lactic acid/100 mL in the equilibrium. The stabilised olives were then subjected to sensory evaluation by 200 consumers, and the results were analysed by ANOVA and multivariate statistical techniques. In a first approach, consumers perceived the spontaneously fermented olives as similar to the potentially probiotic product. However, a biplot based on Canonical Variate Analysis showed differences between them in the Salty and Overall score. When data from the consumer test were assessed by PLS analysis, regardless of the fermentation system, Overall score and Buying predisposition were significantly driven by Appearance, Odour, Salty (negatively), Hardness, and Crispness.